1995
DOI: 10.1093/glycob/5.6.571
|View full text |Cite
|
Sign up to set email alerts
|

Detection in human blood platelets of sialyl Lewis X gangliosides, potential ligands for CD62 and other selectins

Abstract: Activated platelets are known to express P-selectin, a lectin-like adhesion receptor (CD62), through which they bind to sialyl Lewis X (sLex) ligands displayed on the membranes of leukocytes. To determine whether direct platelet-platelet interactions via P-selectin/sLex interactions are also possible, we have examined the ganglioside extract of human blood platelets for the presence of sLex ligands. Using the sensitive method of high-performance thin-layer chromatography (HPTLC)-immunostaining with the monoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 0 publications
1
32
1
Order By: Relevance
“…On the other hand, selectins and PLDs bind differently to gangliosides, another class of acidic glycolipids containing sialic acids. P-and L-selectins have been shown to bind not only sulfated glycolipids but also gangliosides (37,38), whereas we showed that brevican PLD does not bind gangliosides. This suggests that the mere presence of negative charges is not sufficient for the binding of brevican PLD to sulfated glycolipids.…”
Section: Discussioncontrasting
confidence: 61%
“…On the other hand, selectins and PLDs bind differently to gangliosides, another class of acidic glycolipids containing sialic acids. P-and L-selectins have been shown to bind not only sulfated glycolipids but also gangliosides (37,38), whereas we showed that brevican PLD does not bind gangliosides. This suggests that the mere presence of negative charges is not sufficient for the binding of brevican PLD to sulfated glycolipids.…”
Section: Discussioncontrasting
confidence: 61%
“…The sLeX antigen has been detected on the surface of multiple cell types, including granulocytes (particularly neutrophils), monocytes (28,29), platelets (30), natural killer cells (31), activated lymphocytes (32), and helper memory T cells (33), where it may be present on glycoproteins or glycolipids. The sLeX antigen has a critical role in the inflammation process (34).…”
Section: Discussionmentioning
confidence: 99%
“…All tissue procurement was carried out with the supervision and approval of the institutional human investigation committee. 49,50 The total GSL fraction of each tissue was isolated using the procedure of Ledeen and Yu with modification. [49][50][51] Briefly, lyophilized cell powders were extracted with chloroform-methanol (C/M 1:1 [vol/vol]; 100 mL/g dry weight) to obtain a total lipid extract.…”
Section: Leukemic and Normal Peripheral Blood Cellsmentioning
confidence: 99%
“…49,50 The total GSL fraction of each tissue was isolated using the procedure of Ledeen and Yu with modification. [49][50][51] Briefly, lyophilized cell powders were extracted with chloroform-methanol (C/M 1:1 [vol/vol]; 100 mL/g dry weight) to obtain a total lipid extract. Neutral lipids were isolated by anion exchange chromatography (A-25 DEAE-Sephadex; Sigma, St Louis, MO), saponified with 0.3 N methanolic NaOH to remove phospholipids, followed by dialysis against distilled water.…”
Section: Leukemic and Normal Peripheral Blood Cellsmentioning
confidence: 99%
See 1 more Smart Citation